Publishing in indexed journals with a high impact factor. Importance and strategies to achieve this - Juan Ramón García Díaz (Journal of the Selva Andina Animal Science)
Research is a key output area, or substantive process in the functioning of higher education institutions. It interacts harmoniously with teaching and university extension, to achieve quality and integration of the university with society. Research is not concluded until its results are published, even if they are not important and novel, without publication, science does not exist. Ideally, it should be published in indexed journals and, better still, in journals with a high impact factor, which influences the quality, scope and scientific level of the work. These publications are verified, evaluated, replicated and rapidly incorporated into scientific knowledge. University professors and researchers should publish their results in indexed journals, especially those with a high impact factor, because this stratifies and selects scientists, giving them recognition and economic status. It also allows them to achieve relevant achievements, to advance smoothly in their scientific career, to achieve rapid academic promotion and to obtain funding for grants and research projects.